Increased Energy Efficiency in Brazil: an option for a low carbon economy? - Aline Souza Magalhães; Edson Paulo Domingues (Economia Aplicada, 2016)
One of the most discussed effects of economic activity on the environment are climate changes caused by the accumulation of greenhouse gases. Brazil has confirmed voluntary emissions reduction targets and propose Sectoral GHG Mitigation Plans. One of these plans refers to increasing energy efficiency. In this paper, we estimate the impact of this improvement in energy use on the Brazilian economy, considering its productive sectors and families, as well as the emission reduction potential. The results show the importance of energy efficiency policies, both for economic growth and for reducing emissions